Relational Human–Nature Ethics in Indigenous Ritual Practice: The Selametan Ubar Pare among the Baduy Community in Indonesia - Deni Miharja; Iis Badriatul Munawaroh (UIN Sunan Gunung Djati Bandung, 2025)
Climate change poses a global challenge that has prompted the search for alternative mitigation approaches beyond technological solutions and formal policy frameworks, including those grounded in religious practices and indigenous local wisdom. This study analyzes the Baduy worldview through the selametan ubar pare ritual as a form of ecological ethics rooted in intersubjective relations between humans and nature. The research adopts a qualitative approach using ethnographic methods. Data collection involved participant observation and in-depth interviews conducted over a 30-day period within the Baduy community, complemented by systematic documentation of ritual practices, customary institutions, and huma agricultural activities. The findings demonstrate that the Baduy community constructs a relational ontology and epistemology that positions nature not as a passive object but as a living, responsive, and morally agentive relational subject. The community institutionalizes this relationship through pikukuh karuhun and enacts it concretely in the selametan ubar pare ritual, which integrates religious beliefs, traditional ecological knowledge, and sustainable agricultural practices. The ritual functions as a preventive mechanism that limits resource exploitation, regulates planting and harvesting rhythms through the customary calendar, and strengthens social solidarity and community resilience. Accordingly, climate change mitigation in the Baduy context operates not through technocratic interventions but through the internalization of ecological ethics and reciprocal human–nature relations embedded in everyday practice. The implications of this study affirm that indigenous religious ritual practices can serve as an ethical infrastructure for ecological sustainability at the local level. The originality of this research lies in interpreting indigenous ritual as an intersubjectivity-based ecological epistemology and ethic, thereby extending the field of religion and environmental studies while challenging perspectives that reduce indigenous rituals to symbolic, irrational, or premodern practices.